2017
DOI: 10.1055/s-0043-119074
|View full text |Cite
|
Sign up to set email alerts
|

Alpha mangostin Inhibits Hepatic Stellate Cells Activation Through TGF-β/Smad and Akt Signaling Pathways: An in vitro Study in LX2

Abstract: Alpha mangostin inhibits hepatic stellate cells proliferation and activation through TGF-β/Smad and Akt signaling pathways in dose dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
(41 reference statements)
2
21
0
Order By: Relevance
“…The trypan blue exclusion test was performed for the specification of the death/survival of isolated hepatocytes through the destruction of the plasma membrane [18]. In this test, cumene hydroperoxide (a potent oxidizing agent EC50 = 120 µM [19]) was used as a negative control and Gallic acid (a potent antioxidant [20]) was used as a positive control.…”
Section: Evaluation the Cytotoxicitymentioning
confidence: 99%
“…The trypan blue exclusion test was performed for the specification of the death/survival of isolated hepatocytes through the destruction of the plasma membrane [18]. In this test, cumene hydroperoxide (a potent oxidizing agent EC50 = 120 µM [19]) was used as a negative control and Gallic acid (a potent antioxidant [20]) was used as a positive control.…”
Section: Evaluation the Cytotoxicitymentioning
confidence: 99%
“…Specifically, PDAC was chosen as the representative IET model. α-mangostin (α-M), a natural xanthone isolated from the pericarps of mangosteen was selected since it had been reported to reduce liver fibrogenesis without obvious hepatotoxicity 22 . Therefore, we hypothesized it might be also effective in PDAC.…”
mentioning
confidence: 99%
“…This increase in proliferation may due to TGF-β/SMADindependent signaling, as the PI3K/Akt pathway can enhance Akt phosphorylation and increase HSC proliferation. A study by Zang et al showed that TGF-β treatment increased the expression level of the proliferation marker Ki-67 in rabbit cornea cells, and Kang et al found that TGF-β1 treatment at 2 ng/mL at 24 and 48 h enhanced the HSC proliferation, whereas α-MG at 10 μM suppressed this proliferation back to normal, which suggested the inhibitory activity of this substance against HSC proliferation [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…HSCs are located in the perisinusoidal space and contain lipid droplets rich in Vitamin A. In the normal liver, stellate cells remain quiescent and play a role in maintaining the basal balance of the matrix membrane [2,3]. In response to liver injury, these cells receive signals from a wide variety of growth factors, cytokines, lipid mediators, and adipokines to promote survival at the sites of liver injury containing damaged hepatocytes and immune cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation